PERAMALAN JUMLAH PRODUKSI PADI DI PROVINSI SUMATERA BARAT MENGGUNAKAN METODE ARIMA - Baringbing, Meylani; Natasyah, Nabila; saumi, Fazrina (JURNAL GAMMA-PI, 2024)
Rice farming has a major role in the economy and food security, including in Langsa City. The availability and stability of rice production plays an important role in meeting people's food needs. Therefore, forecasting rice production results is crucial in developing resource management strategies, budget allocations and more focused agricultural policies.The main objective of this research is to provide a solid foundation for strategic planning and decision making in the rice farming sector in West Sumatra. By understanding trends and growth patterns in rice production, it is hoped that this research will make a positive contribution to increasing agricultural productivity, farmer welfare, and food security at the local and regional levels.national. The data research method used in this research is annual data on the amount of rice production in West Sumatra Province (in tons). Data on the amount of rice production was obtained from the Central Statistics Agency (BPS). This study focuses on food availability and the agricultural sector in West Sumatra Province by utilizing rice production data from 2018 to 2022. The method applied in this research is the ARIMA method. The following are the steps taken in forecasting using the ARIMA method using Minitab software. The ARIMA(111) model is the best ARIMA model with the smallest MAPE value of 1% for forecasting rice production in West Sumatra Province. Forecasting rice production in West Sumatra Province in 2021 to 2023 is 272,931.95 tons, 271,883.11 respectively. tonnes and 19,554.74 tonnes. The forecast results are lower than the amount of rice production from the previous year, namely 2021 and 2022. Apart from that, from the forecast results it can be seen that rice production in 2023 is lower than in 2022, namely 19,554.74 tons